Avaliação da gestão integrada de resíduos sólidos urbanos em municípios da região metropolitana de Belo Horizonte - Camila Moreira de Assis (2012)
The production of solid waste is inevitable, but it has become a factor in environmental degradation from the onset of urbanization and industrialization. Technical, political, financial and social realities are aspects which guide the adaptation to a better management. Theprocess of Brazilian urbanization was marked by an enormous volume of migration, predominantly of the rural-urban type, but from the 1970s on, there has been an intensification of "urbanurban" displacements wich the formation of metropolitan towns. The occupation of many Brazilian cities has resulted in a loss of control of some strategic sectors,wich the transformation of the urban scenario threaten by risks and social-environmental damage. This work aims to perform a comparative evaluation of the conditions of solid waste management (SWM) in towns in Metropolitan Region of Belo Horizonte (BHMR) through the identification and adaptation of indicators. The BHMR comprises 34 towns and their districts, accounting for nearly 5 million inhabitants. Located in the central region, it exercises great influence, being the political, financial, commercial, educational and cultural center ofMinas Gerais. Documentary research was carried out on the indicators available and those published by researchers, focusing on the evaluation of SWM. Those which were considered relevant and feasible for evaluating SWM in the BHMR were selected. Ranges of variationwere estimated in order to provide a comparison of indicators among the towns. The definition for a situation to be considered "Very favorable" and even Unfavorable" was based on average values published by authors, field work and theoretical knowledge. The strategies were implemented from 2008 to 2011, and included field trips, analysis of the axesof approach that were of interest to SWM, survey of documents (periodicaly updated), records with photographs, interviews and application of questionnaires to several relevant local social actors. The distribuition was made in 5 population brackets as follows adopted.Given the problem and the multiplicity of issues, there are still relatively few studies regarding SWM in the metropolitan regions of Brazil, and in particular about indicators. Each town defines individually what is suitable and affordable according to their budget. The lack of precise, complete and certain information, makes it difficult any thorough understanding ofthat which it is intended. The tendency in the BHMR for a more multidisciplinary approach to the evaluation of SWM has been observed and the use of indicators should be encouraged, since they are important tools for the integrated nature of this system of urban sanitation.